Potential effect of pharmaceutical care to improve outcomes in patients with chronic kidney disease-mineral bone disorder in Sulaimani dialysis centers - Hawkar Qadir Baiz; Tavga Ahmed Aziz; Dana Ahmed Sharif (College of Pharmacy / Mustansiriyah University, 2020)
Objective: the present study was aimed to evaluate the role of pharmaceutical services in improving the outcome of mineral bone disorder in patients with advanced chronic kidney disease. Methodology: One hundred and twenty patients with chronic kidney disease-mineral bone disorder (CKD-MBD)   screened for eligibility, seventy-six patients enrolled in the study and randomly allocated into two groups: pharmaceutical care and usual care, both groups interviewed by the pharmacist using specific questionnaire for assessing the quality of life (QoL). All the drug related problems (DRPs) including drug-drug interactions (DDIs) were recorded by the pharmacist. Blood samples were collected and utilized for analyzing the levels of vitamin D, phosphorous, calcium, albumin and parathyroid hormone at baseline and three months after. The pharmaceutical care group received all the educations about their medications and how to minimize DRPs; improve the QoL. Additionally, the pharmaceutical intervention included correcting the biochemical parameters. Results: Pharmaceutical care significantly improved patients QoL and minimized DRPs and DDIs. It was also effective in improving the biochemical parameters. Conclusion: Pharmaceutical care has a positive impact on improving the outcome of patients with CKD-MBD through attenuating DRPs, improving the biochemical parameters and the QoL.